Implementation of Learning Media Android-Based Integer in Class VI Elementary School - Suci Nurdiyanty Mer; Mulyadi Mulyadi; Fatia Fatimah (International Journal of Educational Dynamics, 2022)
The background of this research is that most teachers have started to integrate technology into the learning process but still needs to be improved. To overcome these problems teachers need to innovate in overcoming problems in the learning process. One of them is the development of android-based learning media with the ADDIE model research approach. Data collection techniques used instruments in the form of interviews, and questionnaires. Collected data were analyzed, practicality, and effectiveness using a predetermined formula. The implementation results obtained, the development of android-based learning media based on the results of the practicality analysis of android-based learning media has a value of 80.00% in the very practical category, and the effectiveness of android-based learning media has a value of 81.64% with a very high category.